Wash the feet of the world with Mother Teresa - Ringma, Charles (Quezon City : Navigators Ministries, 2006)
1. Teresa, Mother, 1910.--Missionaries of charity.--Biography.--I. Title.
Faculty
Keywords: Teresa, -- Mother, -- 1910-1997.; Missionaries of Charity -- Biography